2021
DOI: 10.1371/journal.pntd.0010016
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the potential non-human animal reservoirs and arthropod vectors of the Mayaro virus

Abstract: Improving our understanding of Mayaro virus (MAYV) ecology is critical to guide surveillance and risk assessment. We conducted a PRISMA-adherent systematic review of the published and grey literature to identify potential arthropod vectors and non-human animal reservoirs of MAYV. We searched PubMed/MEDLINE, Embase, Web of Science, SciELO and grey-literature sources including PAHO databases and dissertation repositories. Studies were included if they assessed MAYV virological/immunological measured occurrence i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 98 publications
0
28
0
Order By: Relevance
“…These viruses are responsible for outbreaks and epidemics all over the world. Mayaro virus is considered an emerging arbovirus and increasing number of human's cases has been reported in several Latin American countries (10,12). Currently, there is no large scale and ongoing urban transmission cycle of this virus although it may be eminent in the next years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These viruses are responsible for outbreaks and epidemics all over the world. Mayaro virus is considered an emerging arbovirus and increasing number of human's cases has been reported in several Latin American countries (10,12). Currently, there is no large scale and ongoing urban transmission cycle of this virus although it may be eminent in the next years.…”
Section: Discussionmentioning
confidence: 99%
“…and non-human primates as vertebrate hosts. However, other species, such as from genus Mansonia, Culex, Sabethes, Aedes and also other vertebrate hosts (rodents and reptiles) may be involved in the transmission cycle (12)(13)(14)(15). Once this virus has a large host range and is able to infect various vertebrates and be transmitted by different mosquito vectors, an important concern is its introduction in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…MAYV is more frequently detected in other countries, in addition to Trinidad and Tobago, Brazil, and Peru. It has also been identified in Panama, French Guiana, Colombia, Argentina, Venezuela, and Paraguay [49,50]. Studies have reported MAYV positivity in wild mammals, birds, or reptiles, as well as in domestic animals.…”
Section: Mayaro (Mayv)mentioning
confidence: 99%
“…Also, 12 orders of wildcaught vertebrates, most frequently in Charadriiformes and primate orders, have been identified with MAYV. This alphavirus has been detected in wild-caught mosquito genera, including Haemagogus, Aedes, Culex, Psorophora, Coquillettidia, and Sabethes [49]. Although MAYV has been identified in urban vectors, there is no evidence of sustained urban transmission.…”
Section: Mayaro (Mayv)mentioning
confidence: 99%
“…MAYV is believed to be primarily maintained in enzootic cycles of transmission involving mainly non-human primates such as the Silvery ( Mico argentatus ), Santarem ( Mico humeralifer ), and White ( Mico leucippe ) marmosets, and acrodendrophilic mosquito species as Haemagogus janthinomys , which is also the main vector of YFV in Brazil [ 7 ]. Several other studies have demonstrated that not only other species of vertebrates, but also vectors have been found infected and can potentially participate in MAYV cycles of transmission [ 16 19 ]. Because MAYV and YFV share the same main vector and have a similar enzootic cycle of transmission, MAYV has been historically detected during yellow fever outbreaks reported in the north region of the country [ 7 ].…”
Section: Introductionmentioning
confidence: 99%